ANALISIS KESALAHAN KALIMAT PADA BUKU TEKS PEMBELAJARAN UNGGUL BAHASA INDONESIA SMK/MAK EDISI KURIKULUM MERDEKA TERBITAN BUMI AKSARA - Putri, Fatkha Meilina; Wati, Anggun Sinta (Fakultas Bahasa dan Sastra Indonesia Universitas Jenderal Soedirman, 2024)
This research discusses the analysis of sentence errors in the class X Indonesian language textbook published by Bumi Aksara. The aim of this research is to describe and explain syntactic errors in the areas of phrases, clauses and sentences. The design method used in this research is qualitative research using descriptive analysis. The research data source was taken from the class X Indonesian language textbook published by Bumi Aksara. Data collection techniques are documentation techniques and note-taking techniques. The data analysis carried out consisted of three processes, namely data reduction, data presentation, and drawing conclusions. The research instrument in this research is the researcher himself. The results of the research show that the data found is dominated by errors in language use in the field of syntax in the form of wasted words, inappropriate use of conjunctions, and use of ineffective sentences. Based on the data that has been obtained, the language errors that are often dominantly found in text book writing are syntax errors.